Group II Secretory PLA2: A New Cardiovascular Risk Factor - Krijnen, Paul A.J.; Nijmeijer, Remco; Hack, C. E.; Niessen, Hans W.M. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2006)
Inflammatory mediators contribute significantly to the induction and progression of cardiovascular diseases such as atherosclerosis and acute myocardial infarction (AMI). A mediator that has been shown to play a crucial role in both cardiovascular events is group-II secretory phospholipase A2 (sPLA2-II), as this mediator has been suggested to modulate atherosclerotic plaque formation, for example by increasing the accumulation of intracellular lipids in macrophages and stimulating the formation of foam cells. Furthermore, increased levels of sPLA2-II in the blood form a risk marker for the development of complications of coronary artery disease. In line with this, we recently found that extracellular sPLA 2-II is more abundantly present in the extracellular matrix of atherosclerotic culprit lesions of coronary arteries in patients who developed AMI than in those of patients with stable or unstable angina pectoris. Another important feature of sPLA2-II is its ability to bind to and hydrolyze membrane phospholipids. Notably, sPLA2-II cannot bind to the tightly packed hydrophobic phospholipids in the outer leaflet of a normal membrane, but only to the disarranged or flip-flopped membranes of damaged cells, as is the case in ischemic jeopardized cardiomyocytes. Interestingly, we recently have observed that sPLA2-II cannot only bind to reversible damaged cardiomyocytes but also induces these cells to die, partly by potentiating binding of C-reactive protein and thus inducing an inflammatory response in the ischemically challenged heart. This review will discuss the pros and cons of therapy with inhibitors of sPLA2-II to prevent complications of the process of atherosclerosis, and/or to limit the amount of cell death of cardiomyocytes subsequent to AMI.
Keywords: Vascular Smooth Muscle Cells